Edukasi Pembuatan Semen Cair Kambing di Kelompok Tani Dian Santosa - Inggit Kentjonowaty Inggit; Nisa’us Sholikah; Nurul Humaidah; Sri Susilowati (Jurnal Pemberdayaan Masyarakat, 2023)
The problem faced by breeders in developing crossbreed goats was the lack of male Boer goats stock which is not balanced with the large number of female Peranakan Etawa (PE) goats, as well as the lack of knowledge and skills of breeders in producing liquid semen. The purposed of this community service was to increased the knowledge and skills of breeders in producing liquid goat semen. The method in this program was counseling, training and accompaniment to members of Dian Santosa's breeder group regarding the implementation of Artificial Insemiation (AI) with liquid semen and how to produce liquid semen. The results of the program show that the enthusiasm of the breeders was high by actively participating in counseling and training in semen collection and liquid semen production. The success of the program was realized by increasing the knowledge and skills of breeders to produce liquid semen and the motivation to create a seed bank. The BoerPE seed bank in the future is expected to become a supplier of breeds as well as a buffer income for the Dian Santosa's breeder group.